2012
DOI: 10.2478/s11756-012-0139-1
|View full text |Cite
|
Sign up to set email alerts
|

Body size as an important factor determining trophic niche partitioning in three syntopic rhinolophid bat species

Abstract: We investigated a community of syntopically occurring horseshoe bats (Rhinolophus hipposideros, R. euryale, R. ferrumequinum) in southern Slovakia. The faecal pellets of these bat species were collected in the field and later analysed under a dissecting microscope. The three species studied are known to be very similar as far as their ecology, echolocation and preferred habitats are concerned, but they diverge significantly in their body sizes. In this study, all three species fed predominantly on moths [59–80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…; Andreas et al . ); however, the bats may be partitioning prey at a lower taxonomic level. Lepidoptera dominate the diets of almost all Rhinolophus species studied to date (e.g., Goiti et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Andreas et al . ); however, the bats may be partitioning prey at a lower taxonomic level. Lepidoptera dominate the diets of almost all Rhinolophus species studied to date (e.g., Goiti et al .…”
Section: Introductionmentioning
confidence: 99%
“…High niche overlap in insect prey composition but low niche overlap in insect prey size One likely axis of niche partitioning between the two Sitta species may be food resources, as this axis has been suggested to be the most important axis for coexistence in many cases (e.g. Grant, 1999;Sebastiano et al, 2012), and difference in prey size is an important factor in trophic niche partitioning in closely related sympatric species (Freeman & Lemen, 2007;Andreas et al, 2013). We found that the trophic niche breadth of S. neumayer was wider than that for S. tephronata and that the two nuthatch species do overlap strongly in prey composition, which would suggest that they do not partition resources.…”
Section: Discussionmentioning
confidence: 99%
“…We identified plants and insects through a stereomicroscope (Magnification 6.3-400) using morphological identification keys (Bey-Bienko, 1954, 1964, 1967Harza, 1975;Triplehorn & Johnson 2005). We calculated the following summary statistics for the gut contents: (1) percent frequency for each taxon (%f), where a particular prey category was expressed as the number of occurrences of the category, divided by total occurrences for all categories, multiplied by 100; (2) percent occurrence (%oc), defined as the number of occurrences of the particular prey category, divided by the total gastrointestinal tract samples, times 100; and (3) percent volume (%vol), where percent volume of a particular prey category was expressed as the volume of that prey category divided by the total volume of all prey, times 100 (following Andreas et al, 2013). To that end, excess preservation fluid was initially removed with absorbent paper and then all the gut material belonging to a focal order was poured in a 10-mL cylindrical tube (graduated cylinder).…”
Section: Analyses Of Gastrointestinal Tract Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We expected that all of the length and area measurements of the wing, body and tail of M. blythii would present significantly lower values compared with M. myotis. In other words, we expected to find that the main difference between these species is due to their different sizes and that the two species are simply scaled versions of the same model (Norberg and Rayner 1987;Stockwell 2001;Andreas et al 2013). Then, in a second step we sought to ascertainwhether the differences in the ecology of the two species could be attributed to morphological adaptations, followed by differences in flight performance.…”
Section: Introductionmentioning
confidence: 99%